Analysis of Financial Performance in Manufacturing Companies Using Financial Ratios - Syahputra, Danil; Ningsih, Supiah (International Journal of Economics (IJEC), 2024)
Background: The objective of every company is to generate profit, increase sales and improve the welfare of employees and shareholders. Purpose: This research aims to investigate the impact of sub-manufacturing companies on the Indonesia Stock Exchange on profitability, liquidity, and activity. Method: The study employed a quantitative research method and utilized purposive sampling to select 10 out of 26 companies that met the researcher's criteria. Result: The research results indicate a significant influence between profitability, liquidity, and activity on financial performance (F-test, sig value of 0.000 < 0.05, F table 2.807 > 255.546). The regression model is considered worthy of further research. Additionally, the T-test shows that profitability and liquidity have a significant effect on financial performance, while activity does not.